Kecukupan Ruang Terbuka Hijau untuk reduksi Carbon dioksida (CO2) di Kampus Unesa Jl. Ketintang Surabaya Indonesia - Muzayanah, Muzayanah; Budiyanto, Eko; Hari Purnomo, Nugroho; Hariyanto, Bambang (Universitas Negeri Surabaya, 2024)
Academic activity at the Unesa Ketintang Campus Surabaya Indonesia, to some extent, contributed to the increase of CO2 concentration in Surabaya City. The increase in CO2 concentration can be balanced by green open space. This study aims to determine the adequacy of green open space in Unesa Ketintang Street Campus in reducing CO2 in ambient air. The analysis unit uses a box model. The observation was carried out for six days in July-August 2021. The adequacy of green open space uses the CO2 reduction value (Net_CO2-Con), an indicator of reducing CO2 concentrations. Net_CO2-Con value is the cumulative concentration of CO2 in the surrounding air for 24 hours. The study results show that from 7 observation points, the average CO2 concentration ranges from 417 – 425 ppmV. The CO2 concentration reduction value (Net_CO2-Con) ranges from -19.46 to -87.69 ppmV. The minus sign (-) on the reduction value indicates that the green open space on the Unesa Campus is sufficient to reduce the CO2 concentration in the ambient air.